Electro-based technologies for contaminants removal from soil and effluent targeting further reuses - Ferreira, Ana Rita Lourinho (2018)
This work would not have been possible without the INTERREG SUDOE project 4KET4REUSE - KETs for the removal of emerging contaminants in treated wastewater from the SUDOE area (SOE1/P1/E0253, 2016 – 2019) that funded most of it, which I deeply acknowledge. The Department of Civil Engineering from the Technical University of Denmark (DTU) is also acknowledged for the funding of the study of the arsenic and petroleum hydrocarbons removal from soil. This work has also received funding from the European Union’s Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No. 778045, the IDS-FunMat-INNO Doctoral Programme funded by the KIC EIT-Raw Materials, the Portuguese Polar Programme-PROPOLAR, the Erasmus+ scholarship, which all were a great contribution to carry out this work. Soil and water resources are interconnected, and their protection is essential to Human life. Emerging organic contaminants (EOC) are a large group of unregulated compounds, which presence in both soils and effluents is a matter of major concern with unknown consequences. Thus, in order to reduce environmental and human associated risks, there is a need to develop viable techniques for the removal of these contaminants. In this Ph.D. dissertation, cost-effective key solutions based on electro-technologies were designed and studied for soil and effluent remediation, which are the downstream and upstream sources of the contamination. Soil remediation was focused on EOC and contamination legacy that is more resistant to natural attenuation (arsenic and petroleum hydrocarbons). The effluent treatment was focused on EOC removals and also the possibility to promote phosphorus recovery/reuse, a critical raw material essential to life. The electrokinetic contaminants removal from soil was developed aiming its valorization either in agriculture or as a secondary raw material. Soil treatment was highly dependent on both soil and contaminants properties. More aggressive electro-treatment conditions were designed ex-situ using 1-to 3-compartment electrodialytic reactors with soil stirring. For all the cases, the electric current enhanced contaminants removal. Up to 80% of arsenic was removed from soil in a 2-compartment cell, whereas remediation experiments of EOC achieved at least a 44% removal (mobilized and/or degraded) for three tested set-ups. An in-situ treatment with different electrical current strategies aiming at less soil disturbance was also developed for more sensitive scenarios like agricultural soil and arctic environment. The removal of hydrocarbons in artic soil was challenged by a more recalcitrant contamination, whereas EOC remediation in agricultural soil was enhanced up to a 37% by the electric current. The electro-technologies developed for effluent treatment were designed to promote a safer irrigation and/or environmental discharge. For either the reuse or the removal of phosphorus, together with EOC removal, a reactor with an anion exchange membrane with polarization switch showed to be the best approach developed (up to 15% P recovery and 57-72% of EOC removal). A one-compartment reactor with a sequence of more than two circular-shaped metal mixed oxide coated titanium mesh electrodes, alternated in polarity, was the best approach for EOC removal (up to 90% in 2 hours). This treatment does not require the addition of reagents and represents low energetic costs, making it more environmentally friendly. The technologies based on electrokinetic treatment showed to have a high potential for a wide array of applications, although the selection of the suitable treatment setup should be done case-by-case.